Trend Analysis of Rainfall Characteristics in Kota Tinggi - Harfizi, Aqilah; Iman Elianie,; Nur Farhanah,; Suhaila Sahat, (Multidisciplinary Applied Research and Innovation, 2022)
Rainfall pattern analysis is significant in hydrological studies and it can be used to assess different planning criteria and the management of water supplies. Human activities might have altered the climate system, which reluctantly increased the intensity of rainfall events. This study aims to estimate the upcoming changes of the intensity of rainfall in Kota Tinggi by using a reliable model which is linear of regression and it is also crucial to analyze the evidence of climate change. The data for monthly and annual rainfall was obtained from the Meteorological Department to be analyzed. To show the monthly and annual rainfall trends in Kota Tinggi from 2002 to 2018, graphs are illustrated. Statistical analysis such as ANOVA has been performed in Microsoft Excel to assess significant differences from the data. Based on the assessment, the highest amount of monthly rainfall distribution is in December, with a value of 3371 mm while the lowest amount is in February, 1211 mm. The highest amount of annual rainfall distribution is in 2017, with a value of 2581 mm and the lowest is in 2018, with an estimated total of only 18 mm. The result of this study shows that the mean monthly and annual rainfall data has an irregular pattern and a statistically insignificant trend. Extensive researches and studies using different trend analysis models is recommended to achieve a more accurate result.